PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS E-LEARNING MOODLE DENGAN MODEL PENGAJARAN LANGSUNG DI SMKN 2 TARAKAN - Agus Riyadi, Rahmat; Nur, Mohamad; Ismayati, Euis (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research aims to develop the learning package based on e-learning moodle by using instruction at SMKN 2 Tarakan. This research adapts 4D instructional developmental model by Thiagarajan. They are define, design, develop and disseminate. The developed learning package is validated by the expert and is tried out to the students? of computer and network engineering at SMKN 2 Tarakan as the research subject. The design of the try out uses one group pretest and posttest design. The data is collected through expert judment, observation, test and questionnaire. The data is analyzed by using descriptive analysis. The research analysis of the learning package development can be described as follows: 1) the average score of the validity of developed learning packaget is 3.83. and gets the criteria of very valid; 2) the average score of the practicality ofr the developed learning package is 4.27 and gets the criteria of good and practical; 3) the average score for the effectiveness of the developed learning package which involves the students? activities in the learning process is 3.23, the reliability is 0.93, and get the criteria of very active; students? response for the learning process is 88% and get the criteria of very positive, the result of the students? study result meets get criteria of mastery. The conclusion of this research is the learning package which is valid, practical, and effective. The validity consists of content validity and constructs validity. The practically consists of the easiness in use. The effectiveness gets the positive response, improve the students? activities and mastery in student?s achievement. Keywords: Learning Set, E-Learning Moodle, Direct Instruction.